Bring home the Internet. - Dutta-Roy, A.
In the good old days, the only two-way communications link with a residence was provided by the local telephone company (telco). But the growth of the Internet and the passing, in the United States, of the Telecommunications Act of 1996 have changed that tradition. Today, a competitive local exchange carrier can compete in the turf of the local telco, now called an incumbent local-exchange carrier. In addition, cable TV operators are allowed to offer telephony and Internet access services to their subscribers along with TV programs. The question of who will supply the `last mile' pipe to the home could lead to some of the toughest fights the communications marketplace has ever seen. Winners will gain the revenues from supplying a cornucopia of phone, TV and Internet services. The paper discusses these issues as well as asymmetric digital subscriber line, cable modems, service billing, wireless connections, and power grid use for optical cable laying for communications
Keywords: Internet; Internet access services; TV programs; Telecommunications Act of 1996.; United States; Asymmetric digital subscriber line; Cable TV operators; Cable modems; Competitive local exchange carrier; Optical cable laying; Power grid use; Service billing; Telephony; Two-way communications link; Wireless connections